Phenotype and clinical outcomes of dystrophin associated dilated cardiomyopathy. (25th November 2020) - Restrepo Cordoba, M.A; Wahbi, K; Florian, A; Mogensen, J; Jimenez-Jaimez, J; Climent-Paya, V; Politano, L; Garcia-Alvarez, A; Arad, M; Barriales-Villa, R; Kubanek, M; Lopes, L.R; et al.
Abstract: Background: Mutations in dystrophin gene (DMD) can cause skeletal myopathy and dilated cardiomyopathy (DCM) independently or in combination. Natural history of DMD mutation carriers and dystrophin-associated DCM is poorly understood. Objectives: This study sought to describe phenotype and prognosis of DMD mutations in a large multicenter cohort of Non-Duchenne DMD mutations carriers. Methods: The study cohort comprised 223 individuals with a DMD mutation (83% males, 33±15 years at first evaluation) followed at 26 European centers. Major adverse cardiac events (MACE) were defined as a composite of cardiac death, heart transplant, LVAD implantation, aborted SCD or appropriate ICD shock. Results: At initial evaluation, 85 patients (38%) had DCM (52 in combination with muscular disease) and 92 (41%) had isolated muscular disease. After a median follow-up of 96 months, 112 individuals (53%) had DCM and 20% of the individuals who had normal cardiac function at baseline developed DCM. DCM penetrance by age 30 was 56%. DCM onset was associated with male sex and was independent of the type of mutation, the presence of skeletal myopathy or serum creatine kinase levels. MACE occurred in 11% and 22% individuals from the entire cohort and with DCM respectively, and were more frequent in DCM patients without muscular disease than in those with skeletal myopathy (35.5% vs 17.7%; p=0.04). Among patients with DCM, 18% developed end-stage heart failure and 9% a major arrhythmic event (SCD/aborted SCD/ICD shock/VT). There were not differences in survival between patients with isolated DCM and those with DCM and muscular phenotype. Decreased LVEF and increased left ventricular end-diastolic diameter at baseline were associated with MACE. Atrial fibrillation and neurological events were also frequent. Prognosis of individuals who did not develop DCM was good with 96% survival during follow-up. Conclusions: DCM caused by mutations in DMD is characterized by moderate penetrance but a high risk of MACE, progression to end-stage heart failure and ventricular arrythmias. DCM onset is the major determinant of prognosis in DMD mutation carriers with similar survival irrespectively of the presence of concomitant muscular disease. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Instituto de Salud Carlos III. Contratos i-PFIS: Doctorados IIS-empresa en Ciencias y Tecnologías de la Salud